BASIC ENGLISH UNTUK PEMASARAN PRODUK NELAYAN DESA BASKARA BHAKTI: KESIAPAN EKSPOR PRODUK MELALUI PENGUASAAN BAHASA INGGRIS UNTUK PEMULA - Anggraeni, Diana; Wulansari, Dini; Afandi, Rizky Arif (PEDULI: Jurnal Ilmiah Pengabdian Pada Masyarakat, 2025)
This community service program entitled “Basic English for Fishermen’s Product Marketing in Baskara Bhakti Village: Export Readiness through Beginner-Level English Proficiency” was designed to address the limited English competence among local fishermen that hinders access to international markets. Using a participatory approach involving the village head and fishermen groups, the program developed learning materials in the form of a Basic English module, conversation worksheets, and short instructional videos tailored to the context of seafood product marketing. The implementation showed that fishermen were able to practice simple sentences such as introducing products, describing quality, stating prices, and responding to buyers’ questions, which significantly enhanced their confidence in using English. Positive responses from both participants and community partners confirmed the relevance of the materials, and indirect benefits were also observed as family members, including women and children, engaged with the learning process. The strengths of this program lie in its contextual design, accessibility, and participatory method, while weaknesses include limited vocabulary coverage, short training duration, digital infrastructure constraints, and lack of long-term evaluation. Overall, the program proved to be a strategic solution to support fishermen’s readiness for export by equipping them with practical English skills for global communication